Quadruple primary tumors in a lynch syndrome patient surviving more than 26 years with genetic analysis: a case report and literature review - Zhu, Bosen; Liu, Ming; Mu, Tianhao; Li, Wentao; Ren, Junqi; Li, Xiangtao; Liang, Yi; Yang, Ziyi; Niu, Yulin; Chen, Shifu; Lin, Junqiong (Frontiers in Oncology, 2024)
The incidence of multiple primary tumors(MPTs) is on the rise in recent years, but patients having four or more primary tumors is still rare. Lynch syndrome (LS) patients have a high risk of developing MPTs. NGS sequencing could identify the genetic alterations in different tumors to make a definite diagnosis of uncommon cases in clinical practice. Here, we report the case of a 66-year-old female patient who develops four MPTS between the ages of 41 and 66, that is sigmoid colon cancer, acute non-lymphocytic leukemia, urothelial carcinoma and ascending colon cancer. She has survived for more than 26 years since the first discovery of tumor. Targeted sequencing indicats that she has a pathogenic germline mutation in the exon 13 of MSH2, and her 2020 ureteral cancer sample and 2023 colon cancer sample have completely different mutation profiles. To the best of our knowledge, this is the first case of multiple primary tumors with an acute non-lymphocytic leukemia in LS patients.